2022
DOI: 10.3390/jof8060579
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Reveals Population Structure and Mating-Type Loci in Marssonina brunnea

Abstract: Marssonina brunnea is an important fungal pathogen of poplar trees. We collected 32 M. brunnea f.sp. multigermtubi (MbMu) and three M. brunnea f.sp. monogermtubi (MbMo) isolates from four poplar species in three Chinese regions and performed genome resequencing. An annotation of SNPs of MbMu indicated that the SNPs potentially have a functional effect on 69.2% of the predicted genes. Using the SNP dataset of nonredundant isolates, a structure and principal component analysis revealed that MbMu and MbMo belong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…With the advent of molecular genomic tools and advanced analytical approaches for population surveillance, a detailed insight into the genomic structure of both pathogens and their hosts can now be achieved. This allows inference of key factors that may affect population genomic structures like host‐pathogen interaction and co‐evolution, geographic and temporal dynamics as well as life history traits (Allen et al, 2018; Blasco‐Costa & Poulin, 2013; Cheng et al, 2022; Mei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of molecular genomic tools and advanced analytical approaches for population surveillance, a detailed insight into the genomic structure of both pathogens and their hosts can now be achieved. This allows inference of key factors that may affect population genomic structures like host‐pathogen interaction and co‐evolution, geographic and temporal dynamics as well as life history traits (Allen et al, 2018; Blasco‐Costa & Poulin, 2013; Cheng et al, 2022; Mei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…brunnea f. sp. monogermtubi (MbMo) and E. australis (Ea) are common fungal pathogens of Shanxin, and the genomes of these two fungi have been sequenced in our previous studies (Cheng et al, 2022;Zhao et al, 2020) S1). Sanger sequencing showed that the predicted introns were appropriately spliced, and the cloned sequences were all consistent with predicted gene models, indicating that the four NLP genes were not pseudogenes and were expressed in the early stage of infection.…”
mentioning
confidence: 99%
“…M. brunnea f. sp. monogermtubi (MbMo) and E. australis (Ea) are common fungal pathogens of Shanxin, and the genomes of these two fungi have been sequenced in our previous studies (Cheng et al, 2022 ; Zhao et al, 2020 ). A tBLASTn search with NLP of P. parasitica (GenBank accession no.…”
mentioning
confidence: 99%